Do Firms Value Court Enforceability of Noncompete Agreements? A Revealed Preference Approach - Hiraiwa, Takuya; Lipsitz, Michael; Starr, Evan (The Review of Economics and Statistics, 2024)
Do firms value court enforceability of their workers' noncompete agreements (NCAs)? We leverage a 2020 Washington law that made NCAs unenforceable for workers earning less than $100k per year. If firms value the ability to enforce NCAs in court, then they should give just-below threshold workers raises to reach the threshold, resulting in excess mass just above the threshold. Using administrative data, we find no evidence of bunching, even where efficiency arguments are most plausible. A survey of Washington employment attorneys suggests little bunching because firms rarely need to enforce NCAs and because firms can use other, less restrictive alternatives.